Implementasi Evaluasi Formatif pada Siswa Kelas IV SDN Petukangan Utara 08 Kota Jakarta Selatan - Magdalena, Ina; Khairunnisa, Aura Zahrotun; Pertiwi, Nabila Putri; Rahma, Salsa Nabila (ANWARUL, 2023)
This article is a theoretical study of the implementation of formative evaluation in grade IV students at SDN Petukangan Utara 08. This study aims to find out and describe empirically about: Aspects, techniques and procedures for class assessment carried out by teachers in grade IV students at SDN Petukangan Utara 08 South Jakarta. Evaluation is an important activity carried out by educators in the learning process. By evaluating educators, they can improve their competence in class management both in choosing learning methods, media, teaching materials, and so on which can motivate students to learn. besides that withEvaluation of educators can determine the level of success of their students. Therefore educators must carry out the implementation of evaluation activities correctly. This type of research is a qualitative research using a formative evaluation model developed by Scriven which includes aspects of assessment, assessment techniques, and assessment procedures. The instruments used were observation sheets and interviews. The results showed that: (1) The aspects of the assessment that had been carried out by the teacher included cognitive, psychomotor, and affective aspects, (2) The assessment techniques carried out by the teacher that had been developed were written tests and oral tests. The application of formative evaluation in grade IV is carried out at the beginning or throughout the learning process.